2022
DOI: 10.3390/foods11040552
|View full text |Cite
|
Sign up to set email alerts
|

Olive Cake Powder as Functional Ingredient to Improve the Quality of Gluten-Free Breadsticks

Abstract: The growing demand for high-quality gluten-free baked snacks has led researchers to test innovative ingredients. The aim of this work was to assess the feasibility of olive cake powder (OCP) to be used as a functional ingredient in gluten-free (GF) breadsticks. OCP was used by replacing 1, 2, and 3% of maize flour into GF breadstick production (BS1, BS2, BS3, respectively), and their influence on nutritional, bioactive, textural, and sensorial properties was assessed and compared with a control sample (BSC). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 107 publications
0
8
1
Order By: Relevance
“…The total phenol substance, flavonoid and antioxidant capacity results of bread enriched with green olive pulp were reported as 60.9–105.2 mg Gallic acid equivalent/100 g, 41.9–73.8 mg CE/100 g and 11.9–40.5 mg Trolox Equivalent/100 g, respectively (Marinopoulou et al ., 2020). With increasing concentrations of olive pulp in Gluten‐Free Breadstick formulations, higher total phenol quantity and antioxidant activity results were detected in Gluten‐Free Breadsticks (De Gennaro et al ., 2022). The total phenol quantities of our bread samples were similar to the results of the breads made with green olives by Cedola et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The total phenol substance, flavonoid and antioxidant capacity results of bread enriched with green olive pulp were reported as 60.9–105.2 mg Gallic acid equivalent/100 g, 41.9–73.8 mg CE/100 g and 11.9–40.5 mg Trolox Equivalent/100 g, respectively (Marinopoulou et al ., 2020). With increasing concentrations of olive pulp in Gluten‐Free Breadstick formulations, higher total phenol quantity and antioxidant activity results were detected in Gluten‐Free Breadsticks (De Gennaro et al ., 2022). The total phenol quantities of our bread samples were similar to the results of the breads made with green olives by Cedola et al .…”
Section: Resultsmentioning
confidence: 99%
“…Sensory quality has been reported to be affected by the addition of olive oil by‐products to the food and enriched bread has been reported to have an acceptable score much higher than the sensory threshold (Cedola et al ., 2019). It caused a decrease in the L * and b * values as well as the hardness values of gluten‐free breadsticks containing 3% olive cake powder (De Gennaro et al ., 2022). It has been reported that interactions between polyphenols and fibre, water and starch–gluten matrix cause differences in olive pomace dough (Dahdah et al ., 2024).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The olive oil process generates a solid residue called olive pomace which formed about 35-40% of processed olives (around 2500-2800 t in Iran) [15]. Olive pomace is a rich source of dietary fiber, polyphenols, carotenoids, fatty acids, and minerals [13,16]. However, olive pomace is mainly used as plant fertilizer and biogas [17].…”
Section: Introductionmentioning
confidence: 99%